The Impact of Resilience, Commitment, and Psychological Well-being on Sustainability with Performance as a Mediating Variable: An Organizational Study - Zen, Agustian; Ali, Hapzi; Sastrodiharjo, Istianingsih; Hidayat, Wastam Wahyu (Kuras Institute, 2024)
In a dynamic and competitive era of globalization, organizational sustainability has become a primary focus for various organizations, including Micro, Small and Medium Enterprises (MSMEs). Organizational sustainability involves an organization's ability to continue operating and growing over the long term, despite facing various challenges and uncertainties. This study aims to examine the impact of organizational resilience, organizational commitment, and psychological well-being on organizational sustainability, as well as the role of organizational performance as a mediating variable in the context of MSMEs in Jakarta, Indonesia. The study employs a quantitative approach utilizing SEM-PLS methodology to explore the interrelationships among relevant variables. The research was conducted on 100 MSMEs in Jakarta, Indonesia, using an online questionnaire as the data collection tool. This research found that organizational resilience, reflected in adaptability, innovation, recovery, preparedness, and effective communication, has a positive and significant impact on the sustainability of MSMEs. Additionally, organizational commitment, measured through affective, continuance, and normative commitment, along with employees' psychological well-being characterized by autonomy, environmental mastery, personal growth, positive relationships, life purpose, and self-acceptance also significantly contributes to organizational sustainability.